PERANAKAN CUISINE: CULTURAL WISDOM GROUNDED IN THE MULTICULTURAL IDENTITY OF SATUN TOWN - Thawornwongsa, Sireethorn (Journal of MCU Nakhondhat, 2026)
This research article aims to examine the cultural wisdom embedded in Peranakan cuisine within the multicultural context of Satun Province. It seeks to explain that Peranakan food in the multicultural setting of Satun Province is not merely a form of local cuisine belonging to any single ethnic group; rather, it constitutes a form of cultural capital that reflects the integration of Thai, Chinese, and Malay cultures in Satun. In addition, it serves as a mechanism for the transmission of identity and the maintenance of social relationships within the multicultural society of Satun Province. This study employed a qualitative research design in conjunction with a historical approach. Data were collected through documentary research, oral history, and fieldwork. Field data were gathered by means of in-depth interviews with 10 key informants and participant observation. Data collection continued until saturation was reached in order to obtain comprehensive information, which was then presented through descriptive analysis. The findings reveal that the wisdom of Peranakan cuisine in the multicultural context of Satun Province can be understood through five significant dimensions: 1) Wisdom related to ingredients, which integrates local resource bases; 2) Wisdom related to cooking techniques and the intergenerational transmission of recipes within households; 3) Wisdom related to taste, reflecting the cultural blending of Chinese, Malay, and Southern Thai local traditions; 4) Wisdom related to customs and rituals; and 5) Wisdom related to the construction of contemporary multicultural Satun identity. Peranakan cuisine, therefore, constitutes an intangible cultural heritage grounded in the multicultural identity of Satun, while also fostering pride among younger Peranakan generations in preserving and further developing the wisdom of their ancestors.